The personality of newly graduated and employed nurses: Temperament and character profiles of Swedish nurses. (December 2022) - Mihailovic, Marko; Garcia, Danilo; Amato, Clara; Lindskär, Erik; Rosenberg, Patricia; Björk, Elina; Lester, Nigel; Cloninger, Kevin M.; Cloninger, C.Robert
Abstract: Background: One of the challenges of the 21st century is the high turnover rate in the nursing profession due to burnout and mental illness. From a biopsychosocial perspective, an individual's personality is an important vulnerability-resilience factor that comprises four temperament traits (i.e., a person's emotional reactions) and three character traits (i.e., self-regulation systems). Indeed, different personality profiles are associated to different coping strategies and health outcomes. Objective: We investigated and mapped the temperament and character of Swedish newly graduated and employed nurses' in relation to the Swedish general population and an age-matched sub-sample. Design: In this cross-sectional study, nurses self-reported their personality (Temperament and Character Inventory) at the beginning of their employment. Setting: The data collection was conducted at a hospital in the South of Sweden. Participants: A total of 118 newly graduated and employed nurses ( Mag e = 25.95±5.58) and 1, 564 individuals from the Swedish general population participated in the study. Methods: We calculated T-scores and percentiles for all seven personality dimensions using the Swedish norms ( N = 1, 564). The profiles were calculated by combining high/low percentiles scores in three temperament dimensions (Novelty Seeking: N/n, Harm Avoidance: H/h, and Reward Dependence: R/r) and in the three character dimensions (Self-Directedness: S/s, Cooperativeness: C/c and Self-Transcendence: T/t). Results: Regarding T-scores, the nurses reported moderately lower Novelty Seeking (> 0.5 SD ), slightly higher Harm-Avoidance (about 0.5 SD ), moderately higher Persistence (> 0.5 SD ) and Reward Dependence (> 0.5 SD ), and extremely lower Self-Directedness (> 1 SD ). The prevalence of the most common temperament profiles among the nurses (Swedish general population in brackets) were: 39.80% [10.90%] Cautious (nHR), 21.20% [10.90] Reliable (nhR), and 15.30% [16.50%] Methodical (nHr). The prevalence of the most common character profiles among the nurses were: 31.40% [4.90%] Dependent (sCt), 25.40% [14.40%] Apathetic (sct), and 19.50% [8.80%] Moody (sCT). Conclusions: The analyses of the personality profiles showed that Low Novelty Seeking (79%), high Harm Avoidance (65%) high Reward Dependence (80%), low Self-Directedness (95%), and low Self-Transcendence (60%) were more prevalent among the newly graduated and employed nurses. This may partially explain newly graduated nurses' difficulties at work and high turnover rate. After all, a well-developed character is of special importance when working with patients with serious and terminal illness or under large global crises, such as the current pandemic. Hence, both education at universities and development at work need to be person-centered to reduce stress levels and promote positive self-regulation strategies.